Association of dietary inflammatory index with ocular diseases: a population-based cross-sectional study - Xue Wang; Can Zhang; Haitao Jiang (European Journal of Medical Research)
Abstract Background Our research was designed to investigate the relationship between dietary inflammatory index (DII) and risk of ocular diseases, including glaucoma, cataract, age-related macular degeneration (ARMD), and diabetic retinopathy. Methods We used the National Health and Nutrition Examination Survey (NHANES) data from 2005 to 2008 to conduct this study. The correlation between DII and risk of ocular diseases was examined using weighted multivariable logistic regression analysis, restricted cubic spline (RCS) plots, and subgroup analysis. Results In total, 2885 participants from the NHANES database were included. The DII scores were divided into four group: Q1 (− 4.438–0.386), Q2 (0.387–1.848), Q3 (1.849–3.073), and Q4 (3.074–4.970). RCS shown that there was a U-shaped correlation between DII and prevalence of glaucoma, cataract, ARMD, and diabetic retinopathy. After adjusting for underlying confounding variables, compared to Q1 group, the odd ratios (ORs) with 95 percent confidence intervals (CIs) for glaucoma, cataract, ARMD, and diabetic retinopathy across the quartiles were [0.97 (0.54, 1.75), 1.20 (0.68, 2.11), and 1.29 (0.73, 2.30)], [0.87 (0.56, 1.35), 1.12 (0.73, 1.73), and 1.16 (0.75, 1.80)], [0.85 (0.53, 1.36), 0.66 (0.40, 1.09), and 0.97 (0.61, 1.56)] and [0.86 (0.63, 1.18), 0.89 (0.65, 1.22), and 1.04 (0.75, 1.45)] for DII, respectively. Conclusions Reducing the intake of pro-inflammatory foods may be an effective measure to prevent the onset of ocular disease, including glaucoma, cataract, ARMD, and diabetic retinopathy. However, eating only anti-inflammatory foods is not the best choice.